〔報告〕亜寒帯湿潤大陸性気候における資料保存環境調査―付着菌、空中浮遊菌のサンプリングを中心として― - 吉川 也志保; 佐野 千絵; 石崎 武志 (2011)
The risk of biological deteriorations depends much on the climate and the architectural conditions of buildings which possess cultural properties, books, and documents. The investigation was carried out at the Federal Conservation Center, National Library of Russia, St. Petersburg. Considering the climograph which shows monthly average values of the annual outdoor temperature and relative humidity, there is a lower risk of deterioration by insects and mould in St. Petersburg than in Tokyo. Indoor climate condition of the storage in this library was also far from this risk. However, the range of maximum and minimum values of outside temperature there is quite broad; this may easily cause physical stress to the materials. We performed samplings of surface moulds and air-borne moulds with Cz(Czapek) and MA (Malt extract agar + NaCl 10%) media using an air-sampler (EMD Chemicals Inc,MAS-100). The CFU value inside the storage was always lower than that outside. We detected more xelophilic moulds than hydrophilous moulds inside the storage and found flora with pshycrophilic fungi characteristic in subarctic continental humid climate. Biological damage was not seen during the investigation from April to June, even with high humidity outside. It is possible that the architectural damp course and calorifuge of the traditional style building defend collections from biodeterioration influenced by the outdoor climate.